IMPLEMENTASI SUPERVISI AKADEMIK KEPALA SEKOLAH UNTUK MENINGKATKAN KINERJA GURU - Leniwati, Leniwati; Arafat, Yasir (Graduate Program Magister Manajemen Pendidikan, 2017)
The purpose of this research was to obtain information about the implementation of academic supervision done by the headmaster in order to develop teachersâ€™ performance. This research used qualitative method. Data were collected through interview, observation and documentation. The subjects of this research were the headmaster and the teachers. The results showed that the implementation of the academic supervision was done on three steps were planning, implementation and evaluation. The teachers gave positive responses to the implementation of academic supervision.Â Keywords: Academic Supervision, Headmaster, Teachersâ€™ Performance